The protest activity of Russian youth - Gabriella Witdarmono (Revista on line de Política e Gestão Educacional)
In the present era of evolution, language holds an essential place in the value system of any country. In globalization, there is an interaction on between various nations in politics, science, culture, economics, which results in meaningful changes in national languages and cultures. The present study is based on an empirical study carried out by the authors at the Moscow State University of Technology and Management named after K.G. Razumovsky (PKU), an analysis of the effect of English language on youth (students) in the 2010s. The conclusion is made about the transformation of the youth’s English learning skills and attitudes in the digital society. This present paper shows that beneficial (creative) forms of the effect of English language on Russian youth can assist in forming a productive and functioning culture of communication and interaction between the young people and others, especially in the educational spheres.